2021
DOI: 10.3390/vaccines9080835
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Intention among Healthcare Workers in Saudi Arabia: A Cross-Sectional Survey

Abstract: The COVID-19 pandemic has caused largescale morbidity and mortality and a tremendous burden on the healthcare system. Healthcare workers (HCWs) require adequate protection to avoid onward transmission and minimize burden on the healthcare system. Moreover, HCWs can also influence the general public into accepting the COVID-19 vaccine. Therefore, determining COVID-19 vaccine intention among HCWs is of paramount importance to plan tailor-made public health strategies to maximize vaccine coverage. A structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
(29 reference statements)
4
22
1
Order By: Relevance
“…A study conducted in Saudi Arabia just before the launch of the vaccination campaign indicated that females were less likely to accept the vaccine as compared to males [20]. Similar results were reported in other studies in Saudi Arabia that were conducted after the launch of the vaccination campaign [22,23]. From a global perspective, a systemic review of COVID-19 vaccine intention in 33 countries indicated that males were more likely to accept the vaccine [24].…”
Section: Discussionsupporting
confidence: 75%
“…A study conducted in Saudi Arabia just before the launch of the vaccination campaign indicated that females were less likely to accept the vaccine as compared to males [20]. Similar results were reported in other studies in Saudi Arabia that were conducted after the launch of the vaccination campaign [22,23]. From a global perspective, a systemic review of COVID-19 vaccine intention in 33 countries indicated that males were more likely to accept the vaccine [24].…”
Section: Discussionsupporting
confidence: 75%
“…The willingness to be vaccinated is lower in our study as compared to studies conducted among HCWs in Saudi Arabia where 50.5% and 65% were willing to receive the COVID-19 vaccine [19] , [20] . Furthermore, an online survey conducted across Middle Eastern Region via social marketing indicated that 62.4% (n=543) of the participants would accept COVID-19 vaccine if it became available free of charge [21] .…”
Section: Discussioncontrasting
confidence: 87%
“…We found high COVID-19 vaccination coverage (89%) among HCWs, similar to global reports [21,22]. Despite the smaller number of HCWs interviewed for our study and use of purposive sampling, the high level of uptake is likely a valid representation given the vaccine mandates for this group.…”
Section: Discussionsupporting
confidence: 84%